Impact of indium oxide nanoparticles mouth wash in prevention of human dental enamel caries (in vitro study) - Dhuha Malek Hasan; Maha Jamal Abbas; Batool Hassan Al-Ghurabi (Medical Journal of Babylon, 2023)
Background: Despite the fact that fluoride-based remineralization technologies have dominated preventive dentistry for the past century, new and innovative nanomaterials approaches are transforming the industry. A variety of unique metal nanoparticles (NPs) materials are now be easily available to assist remineralization of the dental enamel surface. Objectives: This study was reported to prevent and treat of dental caries using indium oxide NPs suspension solution application in comparison to de-ionized water and sodium fluoride on human tooth enamel by surface microhardness analysis for the surface dental enamel. Materials and Methods: Field emission scanning electron microscopy, X-ray diffraction, and ultraviolet (UV)-visible absorption spectrophotometer were used to evaluate the physical characteristics of an indium oxide NPs suspension solution that was created by the laser ablation in liquid. Microhardness Vickers test was used to evaluate the microhardness of teeth. Teeth samples were 60 teeth that were divided randomly into two phases; each phase consisted of prevented and treated groups with indium oxide NPs, control-positive group was treated with sodium fluoride, and control-negative group was treated with deionized water. Each group was consisted of 10 teeth. Results: The results showed that there was an increase in microhardness be recorded for both preventive and treatment groups after the application of an indium oxide NPs suspension solution. Conclusion: Laser-prepared indium oxide NPs colloidal suspensions were found to be effective as a remineralizing agent to human dental enamel and thus can be considered as an alternative to sodium fluoride mouth wash.